The elderly population of Rio de Janeiro (Brazil): pilot-study as to the trustworthiness and validity of the mental health segment of the BOAS questionnaire - Veras, Renato P.; Coutinho, Evandro; Ney Jr., George (Revista de Saúde Pública, 1990)
A first step in the pilot-study undertaken as part of a research project on psychiatric morbidity - depression and organic brain syndrome - in the elderly population of Rio de Janeiro is described. The main objective is to "fine-tune" the instrument used (check list of DSM-III) and testing validity of the BOAS questionnaire (Brazilian version of Short-Care). The methodological aspects, and conceptual definitions are focused as well some procedures for the next stage of the project are suggested.